Effect of organic chemistry pedagogies with PEOE,VH, and discussion strategies on students’ achievement in Ekiti State, Nigeria - Victor Oluwatosin Ajayi; Emmanuel Edoja Achor; Emmanuel Eriba Otor (Association for Scientific Computing Electrical and Engineering(ASCEE), 2020)
The study investigated the effect of organic chemistry pedagogies with Predict Explain Observe Explain (PEOE), Vee Heuristic (VH), and discuss strategies on students’ achievement. The study also investigated the interaction effect of treatments and gender on students’ achievement in organic chemistry in Ekiti State, Nigeria. The instrument used for data collection was an organic chemistry achievement test (OCAT). Kuder-Richardson (KR-21) formula was used to test the internal consistency of OCAT, which yielded a reliability value of 0.94. A sample of 308 students comprising 174 boys and 134 girls drawn from 9 schools within 9 Local Government Areas (LGA) out of 16 LGA in the Ekiti State, Nigeria, selected using multi-stage sampling techniques. Two research questions and two null hypotheses guided the study. The research questions were answered using Mean and Standard Deviation scores, while the null hypotheses were tested at 0.05 level of significance using Analysis of Covariance (ANCOVA). The study revealed that PEOE and VH strategies significantly improved students’ achievement [F2, 307=255.284, P0.050] of students in Organic Chemistry. It was recommended among others that since PEOE and VH strategies were found to be effective strategies for improving students’ achievement in Organic Chemistry; Chemistry teacher’s trainee should be trained on the use of PEOE and VH strategies and serving teachers should use it. The curriculum developers should use PEOE and VH strategies to develop and refine the Chemistry curriculum in general and Organic Chemistry in particular.